EFEKTIVITAS PEMBELAJARAN MODEL ALLAN G. BLUMAN DALAM PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA MAHASISWA - Bambang Priyo Darminto (Jurnal Cakrawala Pendidikan, 2011)
Abstract: The Effectiveness of Allan B. Bluman’s Learning Model in the Improvement of Students’ Understanding of Mathematical Concepts. Understanding ma- thematical concepts is one of the important academic aspects. This study aims to improve students’ skills in connecting, communicating and applying mathematical concepts to solve mathematical problems in everyday life. This was an experimental study using the pretest-posttest control group design. The sample consisted of 77 students. The control group learned through the expository method, whereas the experimental group learned through a step by step approach using an interactive multimedia application program of Allan G. Bluman’s model. The results showed that the gain of the experimental group was significantly higher than that of the control group. It can be concluded that the computer-based learning based on Allan G. Bluman’s model enhances the understanding of mathematical concepts. Keywords: mathematical concepts, academic aspect, step by step approach, interactive multimedia, Allan G. Bluman’s model